(untitled) (International Journal of Advanced Research in Science, Management and Technology, 2022)
A journal bearing consist of a shaft (or journal) which rotates freely in a supporting metal sleeve or shell and has no rolling elements. Shell type journal bearings support radial loading only, therefore construction and design is simple whereas understanding of theory and operation may be complex. Its extensive applications are in the field of turbo machinery components such as pumps, compressors and gas turbines as well as in automobile suspension system (transmission and suspension system). The performance of journal bearing depends on pressure distribution, load carrying capacity, frictional force, and speed, viscosity of oil etc. In this thesis, an attempt has been made to present three different commercial lubricant oils such as SAE10W30,SAE 15W40 and SAE 20W40 and their role in determining condition of lubrication (hydrodynamic or hydrostatic), type of pressure distribution and the stresses developed in the bearing under varying loads and speeds. The maximum pressure and Change of viscosity (before and after test) were determined and compared. The maximum stress developed at maximum pressure was 2040 KPa. It is also noticed that, there is an increase in pressure from 0 Kpa to 800 Kpa and then decreases to minimum for remaining rotation of bearing. This clearly indicates the presence of hydrodynamic lubrication in the journal bearing and good to use at higher speeds. It has been found that SAE10W30 bears more load than SAE 15W40 and SAE20W40. Viscosity change shows that temperature has no or little effect. Results prove that an alternate and cheaper lubricant SAE graded oils can be used for improving performance of journal bearing.